Pengaruh fraud pentagon dalam mendeteksi fraudulent financial reporting - Antonius Dwi Maryadi; Pratana Puspa Midiastuty; Eddy Suranta; Anton Robiansyah (Penerbit Goodwood, 2020)
Purpose: This study aims to provide empirical evidence of the influence of financial targets, financial stability, external pressure, institutional ownership, ineffective monitoring, quality of external audits, change in auditors, change of director and frequent number of CEO's picture in detecting fraudulent financial reporting. Research methodology: This study proves that financial targets, external pressure, change in auditors, and frequent numbers of CEO's picture have an effect on detecting fraudulent financial reporting while financial stability, institutional ownership, ineffective monitoring, quality of external audit, and change of director are not influential in detecting fraudulent financial reporting. Results: This study proves that financial targets, external pressure, change in auditors, and frequent numbers of CEO's picture have an effect on detecting fraudulent financial reporting while financial stability, institutional ownership, ineffective monitoring, quality of external audit, and change of director are not influential in detecting fraudulent financial reporting. Limitations: This study used logistic regression analysis using a combined model of Beneish M-Score and Altman Z-Score that still contained an inaccurate classification of fraud and non-fraud. In the research, the R-Square value was low which meant that the ability of independent variables to influence the dependent variable was still low. Contribution: This research is expected to enrich the literature and references that can be used as a reference in other studies as well as in the company. The results of this study are expected to provide a deeper understanding of how to predict fraudulent financial reporting using the Beneish M-Score and Altman Z-Score. Keywords: Fraudulent financial reporting, Fraud pentagon, Beneish M-Score, Altman Z-Score